2022
DOI: 10.1002/rmv.2393
|View full text |Cite
|
Sign up to set email alerts
|

Torque teno virus load as marker of rejection and infection in solid organ transplantation – A systematic review and meta‐analysis

Abstract: Balancing immunosuppression to prevent rejection in solid organ transplant (SOT) recipients remains challenging. Torque teno virus (TTV), a commensal non-pathogenic virus, has been proposed as marker of functional immunity: higher loads correspond to over-immunosuppression, and lower loads to under-immunosuppression. This review offers an overview of the current evidence of the association between TTV-load and infection and rejection after SOT. A systematic literature search strategy, deposited in the PROSPERO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 48 publications
2
44
1
Order By: Relevance
“…We found no relationship between any of these tacrolimus exposure variables and TTV burden. We also did not find that the mean tacrolimus levels were related to TTV load as in other studies in kidney transplantation [13,19,25], unlike Gorzer et al in lung transplants [24]. Moreover, different from previous studies, we analyzed the relationship between TTV load and exposure to mycophenolic acid by measuring the gold standard AUC-MPA.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We found no relationship between any of these tacrolimus exposure variables and TTV burden. We also did not find that the mean tacrolimus levels were related to TTV load as in other studies in kidney transplantation [13,19,25], unlike Gorzer et al in lung transplants [24]. Moreover, different from previous studies, we analyzed the relationship between TTV load and exposure to mycophenolic acid by measuring the gold standard AUC-MPA.…”
Section: Discussioncontrasting
confidence: 56%
“…So far, it is not known precisely which immunosuppressive-related variables influence TTV levels. Some studies have linked higher doses of antimetabolite or CNI drugs or higher CNI blood levels to higher blood TTV loads, but this has not been demonstrated in all studies [13,19,[24][25][26]. Van Rijn et al reported that patients treated with tacrolimus showed higher TTV loads than those under cyclosporine [21].…”
Section: Introductionmentioning
confidence: 99%
“…15 The literature also contains evidence that TTV may serve as a SOT prediction marker for infection and rejection. 8,16,17 This study's primary goal is to confirm and gather new knowledge of the idea that TTV load may be identified as measure of functional immunity, also known as response to vaccination against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“… 15 The literature also contains evidence that TTV may serve as a SOT prediction marker for infection and rejection. 8 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…The TTV DNA load in the systemic compartment behaved as a surrogate marker of the net state of immunosuppression in a pivotal study recruiting solid organ transplant recipients (SOT) 4 , which largely reflected the crucial role of adaptive T cell immunity in the ultimate control of TTV replication 2 . A large body of experimental evidence gathered in the SOT setting supports the assumption that either high or increasing blood TTV DNA levels after transplantation associate with the occurrence of certain infectious events, whereas the opposite holds true for acute rejection [7][8][9] . In the allogeneic hematopoietic stem cell transplantation setting (allo-HSCT), the plasma TTV DNA load appears to correlate with the degree of T cell reconstitution early after transplantation (<day 100), whereas it correlates with the level of immunosuppression afterward [10][11][12] .…”
Section: Introductionmentioning
confidence: 96%